Call for Asymmetric Health Decentralisation in Indonesia - Nugroho, Arief Priyo; Handayani, Sri (Jurnal Borneo Administrator, 2022)
Disparities, Inequalities and inequities are still significant problems after decades of experiencing health decentralisation. This study arranges massive issues on health decentralisation to endorse improvement. The analysis offers insight into decentralisation practices in Indonesia to perform health affairs. A systematic review approach was practised to identify the Scopus database and PubMed MEDLINE from 1999 to 2020, using the terms "health" and "decentralisation." Inclusion criteria were final manuscript, full-text access, and elaborate health administration in the decentralised era. Non-journal articles and non-Indonesia research sites were applied as exclusion criteria. The study analysed 32 reports through Vosviewer tools to confirm health decentralisation trends based on word frequency mentioned in the abstract. Using Atlas.ti qualitative apps tools, the full text of the identified manuscript was analysed into the categorisation of main decentralisation issues; 1) intergovernmental relations, 2) fiscal capacity, 3) regional capacity and capability to elaborate on implementation gap, obstacles, and pros and cons of Indonesia's experience in health decentralisation. The study found that changing decentralisation patterns that mismanaged unequal distribution of health resources raises inequality issues. Second, there is conflictual relation between national and regional health administration-sandwich function caused by the unclear division of government authority. Third, the health policy necessity of a symmetrical approach to coping with regional disparities in fiscal capacity, local government capacity, and capability to provide health services, and inequity problems follow. Moreover, various specific local needs and contexts do not fit in with national health policy. In this context, an asymmetrical approach to managing health answers diverse context responses in implementing decentralisation and inequality and inequity issues.